The Difference of KTSP and Kurikulum 2013 Implementation, Family Environment Toward Career Choosing Readiness - Theodora, Berta Dian; Marti'ah, Siti (Dinamika Pendidikan, 2017)
This research aims to prove: 1) the differences of students’ readiness in choosing a career in students in schools that apply KTSP curriculum with students in schools that apply kurikulum 2013; 2) the differences of the influences of supporting family environment with unsupporting family environment for students’ career choosing; 3) the influence of curriculum that receives family support for students’ career choices. The samples of the study were 355 students from 12 schools in Depok. Data analysis tool used two way anova with interaction. The prerequisite test used normality test and homogenity test. The result of the research shows that: 1) there is no significant difference of curriculum used in school to the students’ career choice readiness, 2) there are significant differences between students who have supporting family environment with students who have less supporting family environment to students’ career choice readiness, 3) there is a significant difference when schools with curriculum work together with family environments to support students in choosing their careers.